Die Entdeckung des Christentums in der Wissenschaft des Judentums - Hasselhoff, Görge K. (Studia Judaica (Walter de Gruyter & Co.) ;, 2010)
This collective volume explores an aspect of the "science of Judaism" which has received little attention up until now. In common use, this term is almost exclusively associated with the scholarly analysis of Judaism. In contrast, the authors of this volume illuminate the different encounters of Jewish scholars with Christianity and the impact of these encounters on the establishment of their Judaism.